Amalgamating Spirituality with Education for Harmonious Exchange and Deepened Wisdom - Pallavi Pathak (Yayasan Rumah Peneleh, 2019)
This article examines the balance between education and spirituality for harmonious exchange and deepened wisdom. Literature studies with the spiritual approach are used in this study. By reconnecting spirituality and education, we can develop an integrated education system that allows students to connect mentally between the intellectual, emotional and spiritual dimensions. Truth, meaning, and the real power of life are within us, and we must release the soul to unleash the real potential. When spirituality is fully embraced in the education system, it will foster a dynamic balance within the students themselves. Keywords: education, spirituality, balance, wisdom